2021
DOI: 10.3390/polym13193231
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Maize Starch Enhanced with High-Voltage Electrical Discharge (HVED) Instead of Thermal Treatment

Abstract: The aim of this research was to explore the use of a high-voltage electrical treatment (HVED) as a substitute for heating during the phosphorylation of maize starch. Starch was treated with HVED, phosphorylated with Na2HPO4 or Na5P3O10 with and without thermal treatment and phosphorylated in combination with HVED prior to and after the chemical modification. When starch was phosphorylated with Na2HPO4, HVED was more efficient in catalyzing reaction (3.89 mg P/kg for 30 min HVED in relation to 0.43 mg P/kg for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(38 reference statements)
0
0
0
Order By: Relevance
“…In other studies, high-voltage electrical discharges have been proposed as a source of energy used during phosphorylation. It was found that such starch treatment has a positive effect on the modification efficiency, phosphorus content, and functional properties, including water absorption, solubility, and rheological characteristics of the finished preparation [34].…”
Section: Monostarch Phosphate (E 1410)mentioning
confidence: 99%
“…In other studies, high-voltage electrical discharges have been proposed as a source of energy used during phosphorylation. It was found that such starch treatment has a positive effect on the modification efficiency, phosphorus content, and functional properties, including water absorption, solubility, and rheological characteristics of the finished preparation [34].…”
Section: Monostarch Phosphate (E 1410)mentioning
confidence: 99%